TINGKAT KECEMASAN WANITA YANG MENDERITA PENYAKIT HIV/AIDS DI YAYASAN GENTA SURABAYA - LELLY APRILIA VIDAYATI (NHM PRESS, 2019)
HIV/AIDS is a collection of symptoms of diseases caused by the immune system that are acquired (not congenital) caused by Human Immunodificiency Virus, which cause anxiety. From the results of the preliminary study showed that all experienced anxiety. Objective of the study is to describe the level of anxiety of women who suffer from the disease of HIV/AIDS in the foundation Genta Surabaya. Method use is descriptive research, using primary and secondary data. The variable in this study is the level of anxiety in women who suffer from HIV/AIDS. Collecting data is using questionnaires with a total population of 30 women suffering from HIV/AIDS. Analysise use univariate. Of the research results obtained from 20 women who have HIV/AIDS, most of the anxiety being experienced as many as 15 women (75%), and small portion experienced mild anxiety as many as 2 women (10%), severe anxiety 3 women (15%). For women with HIV/AIDS more often follow is activiting such as counseling, groups, more open to the family or friends, counseling on health workers to be struck with illness and emergencies can be reduced. For health professionals the results of this study can be used as input and new information about the problems of Anxiety Levels in Women Who Suffer from HIV / AIDS, resulting in medical treatment there is no discrimination for people with HIV / AIDS. So that the level of anxiety in patients is not increased and life expectancy for any high.